Spanish Medical Aid Committee : inter-departmental correspondence (copy) - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0033-001 DR. H.B. MORGAN. MR. H.V. TEWSON. Social Insurance. 29th November, 193. Spanish Medical Aid Committee. Thank you very much for the information on the two Institutions in France, of which I enquired on behalf of the Spanish Medical Aid Committee. The information is just what I wanted, and if Mr. Schevenels can give us any further information I will be glad. I know that at present the Trustees are not prepared to make any grant in such circumstances. HBM/EKK/76. 292C/946/2/33